Manufacturing and testing of spline geometry using carbon fiber reinforced composite - Jambor, Eric, author; Bradley, Thomas, advisor; Radford, Donald, committee member; Heyliger, Paul, committee member (Colorado State University. Libraries, 2016)
A model and manufacturing process for the design of carbon fiber reinforced composite spline shafts is developed and validated to investigate the feasibility of using composite splines for use in power transmission applications. Composite torque tubes for power transmission have been employed in various industries for over three decades and have shown up to a 50% mass decrease compared to steel shafts designed for the same use. One limiting factor for the amount of weight reduction achievable is the mechanism used to transfer power to and from the composite tube. Most composite shafts use adhesive bonding, fasteners, press fits, or some combination to join a steel or aluminum yolk or spline to the end of the tube. This research will investigate the feasibility of eliminating these mechanisms by replacing them by molding in splines to the composite torque tube. This will additionally reduce part count and manufacturing time as well as eliminating the heavy metal inserts. To achieve this, an analytical model is developed to investigate the strength of composite spline teeth of involute geometry as well as a composite torque tube. Due to the complex nature of designing with composites these models are supplemented by material models using a composite software package and finite element models (FEM). The involute splined shaft was then manufactured using an iterative approach to refine the sample quality and tested in torsion to failure. Although the peak failure torque had a large range over the samples it can be concluded that with improvements in the manufacturing process using molded composite splines is a feasible method of torque transfer. This can be concluded from the failure modes of the splined shaft as they indicate that the splines were able to adequately transfer the load to the torque tube.